2014
DOI: 10.1080/09168451.2014.882759
|View full text |Cite
|
Sign up to set email alerts
|

A fungal prenyltransferase catalyzes the regular di-prenylation at positions 20 and 21 of paxilline

Abstract: A putative indole diterpene biosynthetic gene cluster composed of eight genes was identified in a genome database of Phomopsis amygdali, and from it, biosynthetic genes of fusicoccin A were cloned and characterized. The six genes showed significant similarities to pax genes, which are essential to paxilline biosynthesis in Penicillium paxilli. Recombinants of the three putative prenyltransferase genes in the cluster were overexpressed in Escherichia coli and characterized by means of in vitro experiments. AmyG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In contrast, incubation of JanD with 1 gave a mixture of diprenylation products 7a and 7b . Compound 7b is a product in the reaction of prenyltransferase AmyD (a homologue of LtmE) and is one of the putative intermediate in lolitrem biosynthesis. On the other hand, PaxD converted 1 into diprenylpaxilline ( 7a ) quantitatively, while 3 was a good substrate of PaxD to afford 4 and a small amount of a regioisomer.…”
mentioning
confidence: 99%
“…In contrast, incubation of JanD with 1 gave a mixture of diprenylation products 7a and 7b . Compound 7b is a product in the reaction of prenyltransferase AmyD (a homologue of LtmE) and is one of the putative intermediate in lolitrem biosynthesis. On the other hand, PaxD converted 1 into diprenylpaxilline ( 7a ) quantitatively, while 3 was a good substrate of PaxD to afford 4 and a small amount of a regioisomer.…”
mentioning
confidence: 99%
“…A recombinant N‐terminal His 6 ‐tagged LtmE(PT2) was successfully overexpressed in E. coli (Figure S5). When LtmE(PT2) was incubated with 8 , corresponding diprenylated product 9 was detected (Figure S7); this suggested that 9 was an intermediate leading to lolilline. Compound 9 was also produced by an enzymatic reaction with SpdE(PT2) (Figure D).…”
Section: Figurementioning
confidence: 75%
“…Notably, SpdE is a unique chimeric enzyme comprising two prenyltransferase domains homologous to PaxC (identify; 46 %) and AmyD (69 %): the former catalyzes a geranylgeranylation of indole‐3‐glycerol phosphate, followed by elimination of glyceraldehyde 3‐phosphate, thereby yielding 3‐geranylgeranyl indole . The latter mediates diprenylation of 8 . Each domain is tentatively defined as SpdE(PT1) (N‐terminal) and SpdE(PT2) (C‐terminal) hereafter.…”
Section: Figurementioning
confidence: 99%
“…Prenylation of noncyclic carbons by aromatic PTs is unusual but not unprecedented. 12 To date, the products of seven genes encoding these tailoring IDT PTs have been functionally analysed in vivo (PaxD from Penicillium paxilli, 13 AtmD required for aflatrem biosynthesis in Aspergillus f lavus, 14 JanD for shearinine biosynthesis in P. janthinellum, 15 PtmD and PtmE for penitrem biosynthesis in P. simplicissimum, 16 LtmE and LtmF for lolitrem biosysnthesis in Epichloe festucae 11 ), and five have been characterised in vitro (PaxD, 15,17,18 AtmD, 17 JanD, 15 PtmE 16 and AmyD 18 ). Notably, all the IDT PTs analysed to date decorate paspaline-derived IDT skeletons (Fig.…”
Section: Introductionmentioning
confidence: 99%